Recognition of grape leaf diseases using MobileNetV3 and deep transfer learning - Yin, Xiang; Li, Wenhua; Li, Zhen; Yi, Lili (International Journal of Agricultural and Biological Engineering, 2022)
Timely diagnosis and accurate identification of grape leaf diseases are decisive for controlling the spread of disease and ensuring the healthy development of the grape industry. The objective of this research was to propose a simple and efficient approach to improve grape leaf disease identification accuracy with limited computing resources and scale of training image dataset based on deep transfer learning and an improved MobileNetV3 model (GLD-DTL). A pre-training model was obtained by training MobileNetV3 using the ImageNet dataset to extract common features of the grape leaves. And the last convolution layer of the pre-training model was modified by adding a batch normalization function. A dropout layer followed by a fully connected layer was used to improve the generalization ability of the pre-training model and realize a weight matrix to quantify the scores of six diseases, according to which the Softmax method was added as the top layer of the modified networks to give probability distribution of six diseases. Finally, the grape leaf diseases dataset, which was constructed by processing the image with data augmentation and image annotation technologies, was input into the modified networks to retrain the networks to obtain the grape leaf diseases recognition (GLDR) model. Results showed that the proposed GLD-DTL approach had better performance than some recent approaches. The identification accuracy was as high as 99.84% while the model size was as small as 30 MB. Keywords: grape leaf diseases, real-time recognition, deep transfer learning, MobileNetV3 DOI: 10.25165/j.ijabe.20221503.7062 Citation: Yin X, Li W H, Li Z, Yi L L. Recognition of grape leaf diseases using MobileNetV3 and deep transfer learning. Int J Agric & Biol Eng, 2022; 15(3): 184–194.